Islay And The Economy Of Southern Peru In 19th Century - Bonilla, Heraclio (1974)
This article notes the specificity of the regional economic history of Southern Peru, which in 1780-1840 experienced an important economic growth while the rest of the Viceroyalty of Peru was in crisis. This important fact is not well known because of the lack of research on regional economy. It presents data on the dynamics of international markets and its relation with the southern economy. Finally, the article argues some problems related to the general development of the Peruvian economy.